NGABEN : KETIKA KEMATIAN HANYA SEMENTARA - Wegig Murwonugroho; Agus Nugroho Ujianto; Arief Datoem (Universitas Trisakti, 2006)
AbstractGenerally in every funeral ceremony , people are crying or emotionally weeping. But it is not happened in Bali. Ngaben a cremation ceremony for Hindu Balinese, become a boisterous party - a joy parade. It becomes a mass party that is do wild, yet so spiritual. For Hindu Balinese, a body is a temporary shell for an eternal soul. When man dies, the soul , with its five elements, has to be released from the body and then fly back to its macrocosm. The soul will might go throuh several kind of hell, spen some time in heave, and reincarnated in the different body. There is no weeping, due to the creamtion is the expected moment for the soul and also the member s of the family, release from mortal life to ascend to a state of ultimate oneness with God AbstrakSetiap upacara kematian biasanya diiringi dengan isak tangis dan ratap yang tak berkesudahan, namun tidak demikian di Bali. Ngaben, upacara pembakaran mayat Hindu Bali, menjadi ajang pesta kebahagiaan yang riuh. Menjadi pesta masal yang terkadang terlihat begitu liar namun sangat sakral. Bagi orang Hindu Bali, tubuh adalah tempat tinggal sementara bagi jiwa yang abadi,Ketika manusia mati, maka sang Jiwa beserta kelima unsurnya harus melepaskan diri dari sang tubuh untuk kembali menyatu dengan alam makrokosmosnya. Jiwa itu akan melewati beberapa neraka, mencicipi surga, lalu akan dibangkitkan lagi dalam tubuh yang lain di dunia. Tak ada ratapan, karena peristiwa pembakaran inilah yang paling ditunggu oleh sang jiwa dan sanak saudara, membebaskan diri dari segala yang fana untuk berpulang menyatu kepada Hyang Widh